Self-Assembly of Cholesterol-Containing Water-Soluble Polymers - Shin-ichi Yusa (International Journal of Polymer Science)
Self-assembly of amphiphilic polymers containing cholesteryl groups has proved to be attractive in the field of nanotechnology research. Some cholesterol derivatives are known to form ordered structures which indicate thermotropic and lyotropic liquid-crystalline, monolayers, multilayers, micelles, and liposomes. This paper involves the synthesis and characterization of various kinds of amphiphilic polymers bearing cholesteryl moieties.